Why Marcos Pa Rin! - Reyes, Miguel Paolo P.; Jose, Ricardo T. (Kasarinlan: Philippine Journal of Third World Studies, 2018)
This introduction explains how the Third World Studies Center (TWSC) of the College of Social Sciences and Philosophy, University of the Philippines (UP) Diliman decided to hold the public forum series “Marcos Pa Rin! Ang mga Pamana at Sumpa ng Rehimeng Marcos (Marcos Still! The Legacy and the Curse of the Marcos Regime),” thereafter introducing the contents of this issue that were drawn from or linked to that series.
Keywords: Ferdinand Marcos; dictatorship; martial law; Marcos loyalists; propaganda